2012
DOI: 10.1021/ja308888c
|View full text |Cite
|
Sign up to set email alerts
|

Guiding the Design of Synthetic DNA-Binding Molecules with Massively Parallel Sequencing

Abstract: Genomic applications of DNA-binding molecules require an unbiased knowledge of their high affinity sites. We report the high-throughput analysis of pyrrole-imidazole polyamide DNA-binding specificity in a 1012-member DNA sequence library using affinity purification coupled with massively parallel sequencing. We find that even within this broad context, the canonical pairing rules are remarkably predictive of polyamide DNA-binding specificity. However, this approach also allows identification of unanticipated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 55 publications
1
96
1
Order By: Relevance
“…Fluorescence intensity is proportional to the association constant between hairpin polyamide and the underlying DNA sequence (20,21). Sequence specificity can also be determined with NGS by solution-based systematic evolution of ligands by exponential enrichment sequencing (SELEXseq) or Bind-n-sequencing approaches (25,38,39). In the NGS-based approaches, a polyamide with an affinity handle, such as biotin, is incubated with duplex DNA (a library bearing all 10 12 sequence permutations of a 20-bp site).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescence intensity is proportional to the association constant between hairpin polyamide and the underlying DNA sequence (20,21). Sequence specificity can also be determined with NGS by solution-based systematic evolution of ligands by exponential enrichment sequencing (SELEXseq) or Bind-n-sequencing approaches (25,38,39). In the NGS-based approaches, a polyamide with an affinity handle, such as biotin, is incubated with duplex DNA (a library bearing all 10 12 sequence permutations of a 20-bp site).…”
Section: Resultsmentioning
confidence: 99%
“…We turned to in vitro cross-linking experiments to determine whether the differences between the specificity of 3 and 4 were due to more efficient enrichment of high-affinity sites, as is often observed in SELEX experiments (25). In cross-linking experiments, we have previously shown that 4 displays higher specificity for a sequence with a single base-pair mismatch, 5′-AAGAGGAAG-3′ than a sequence with double base-pair mismatch to the seed motif 5′-AAGAGGAGG-3′ (31), where the locations of the mismatches are highlighted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the large-scale analyses of DNA sequence specificities, we performed Bind-n-Seq 30,31,35 experiments with a next-generation sequencer, Ion PGM, with a library of oligomers containing randomized 21-mer. Polyamides 1-5 were biotinylated for this assay to yield polyamides 6-10 by following a previously reported procedure.…”
Section: Bind-n-seqmentioning
confidence: 99%
“…[25][26][27][28][29] Sequence specificities of Py-Im polyamides have also been investigated by using high-throughput sequencing. [30][31][32] Here, we designed and synthesized thirteen Py-Im polyamides ( Fig. 1) to investigate the utility of the AO unit with respect to affinity toward a DNA sequence, sequence specificities of DNA binding, aqueous solubilities, and cell permeabilities.…”
Section: Introductionmentioning
confidence: 99%